From words to wealth: Decoding the language markers and compositions of shop names in Banda Aceh - Silviyanti, Tgk Maya; Yusuf, Yunisrina Qismullah; Akmal, Saiful (Humanities, Arts and Social Sciences Studies, 2024)
This qualitative study examines the names of 100 local and independent businesses to study the linguistic diversity and features of the linguistic landscape in Banda Aceh, Indonesia. The names here refer to those written in specific languages used in Aceh (Indonesian, Acehnese, English, Arabic, and other indigenous languages spoken in the province). The data was collected from five main roads, capturing the shop names for analysis. The results show that English is the dominant language choice, composing a majority of 45% of signage, showing the influence of globalization and the desire for international appeal. While English appears to convey prestige, some businesses blend it with Indonesian or Acehnese, connecting with local culture and engaging diverse audiences. This deliberate language choice reflects a commitment to cultural preservation and authentic customer experiences. Meanwhile, diverse linguistic combinations, emphasizing global influences, cultural preservation, and strategic branding, were also revealed. The most prevalent linguistic structure of signs is product+X (57%), which highlights product types, followed by place+X (14%) which emphasizes regional or cultural identity. In addition, a name/person’s name+X establishes a personalized connection (6%). Finally, in language markers, shop names reveal globalization’s prevalence and demonstrate efforts to convey a global image. The revitalization marker reflects the commitment to the Acehnese language and cultural pride. Identity markers, which include place, name, abbreviation, product, plant name, and brand, establish trust, familiarity, and resonance, creating a dynamic linguistic and cultural landscape where businesses steer global influences and local heritage to connect authentically with customers. To conclude, shop names in Banda Aceh illustrate a vibrant linguistic and cultural environment where businesses use global influences and local heritage to create meaningful bonds with customers.